PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IIISD NEGERI 3TANJUNG BELIT KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Roimah Roimah; Zariul Antosa; Lazim.N Lazim.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack:The research carried out base on the lowly of the result of science subject in grade 3th SDN 3Tanjung Belit which is about 61,60 within minimal completeness criterion stated is 65. Among 20 student, there was only 9 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on science of the three graders in SDN3Tanjung Belit with the application of make a match model. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of make a match model it was abtained student’s outcomes in UH I within average 61,60(improved from basic score 24,18%). The average score form UH II was 81,25 (improved 31,89%). Teachers activities results in the first meeting of the first cycle was 62,50% (good category), and then 70,83% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 87,50% (very good category) and then 91,66% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 54,16% (enough category), 62,50% (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 75% (good category), 83,33% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation of model kooperatif tipe make a match canbe improving IPA learning in three graders at SDN 3Tanjung Belit.Keywords :Cooperatif tipe Make a match, the Result Of IPA Studies.